Moisture sorption isotherms and thermodynamic properties of passion fruit seeds (Research, Society and Development, 2020)
The objective of this work was to determine the adsorption isotherms of sweet passion-fruit seeds, select the mathematical model that best describes the hygroscopic behavior of these seeds and estimate the integral isosteric heat, the differential entropy and Gibbs free energy to the conditions studied. The equilibrium moisture content of the seeds was obtained by the static-gravimetric method. To condition the equilibrium environment, the seeds were placed in sealed containers containing different saturated saline solutions and placed in chambers type B.O.D. regulated at temperatures of 10, 20, 30 and 40 ºC. Analyzing the results obtained conclude that: The equilibrium moisture content of passion-fruit seeds is directly proportional to water activity and decreases as the temperature increases; Among the models tested, the Chung Pfost model is the one that best represents the hygroscopicity of sweet passion-fruit seeds; With the reduction of the moisture content of the seeds, the integral isosteric heat of adsorption, the diﬀerential entropy and the Gibbs free energy increase; The adsorption process of sweet passion-fruit seeds is controlled by enthalpy.